3D brain angiogenesis model to reconstitute functional human blood–brain barrier in vitro. Issue 3 (4th December 2019) - Lee, Somin; Chung, Minhwan; Lee, Seung‐Ryeol; Jeon, Noo Li
Abstract: The human central nervous system (CNS) vasculature expresses a distinctive barrier phenotype, the blood–brain barrier (BBB). As the BBB contributes to low efficiency in CNS pharmacotherapy by restricting drug transport, the development of an in vitro human BBB model has been in demand. Here, we present a microfluidic model of CNS angiogenesis having three‐dimensional (3D) lumenized vasculature in concert with perivascular cells. We confirmed the necessity of the angiogenic tri‐culture system (brain endothelium in direct interaction with pericytes and astrocytes) to attain essential phenotypes of BBB vasculature, such as minimized vessel diameter and maximized junction expression. In addition, lower vascular permeability is achieved in the tri‐culture condition compared to the monoculture condition. Notably, we focussed on reconstituting the functional efflux transporter system, including p‐glycoprotein (p‐gp), which is highly responsible for restrictive drug transport. By conducting the calcein‐AM efflux assay on our 3D perfusable vasculature after treatment of efflux transporter inhibitors, we confirmed the higher efflux property and prominent effect of inhibitors in the tri‐culture model. Taken together, we designed a 3D human BBB model with functional barrier properties based on a developmentally inspired CNS angiogenesis protocol. We expect the model to contribute to a deeper understanding of pathological CNS angiogenesis and the development of effective CNS medications. Abstract : A novel strategy mimicking CNS angiogenesis to develop 3D in vitro human blood‐brain barrier (BBB) model is described. Lee and coworkers have applied a developmentally inspired BBB tri‐culture protocol to reconstitute physiologically relevant BBB‐specific phenotypes including efflux transporter. This perfusable 3D BBB vasculature model showing functional barrier system has potential applications in further CNS drug transport studies.